Avaliação quantitativa do tratamento da água utilizando os coagulantes tanino e cloreto férrico - Silva, Ingrid Rodrigues Guimarães (2019)
In order to make raw water suitable for human consumption, a conventional process that takes place inside water treatment plants is started. Inorganic coagulants of chemical origin, made up of iron and aluminum salts, such as aluminum sulphate (Al2(SO4)3), Ferric sulfate (Fe2(SO4)3) and Ferric Chloride (FeCl3), however, several problems are detected due to its use. Several studies have been carried out in the study of organic coagulants aiming to improve the treatment of water for the human supply, as well as the residues generated during this process. The objective of this work was to determine and compare the characteristics of the water generated in the coagulation / flocculation / sedimentation / filtration process using both the organic coagulant tannin and the inorganic coagulant Ferric Chloride. The treatments were carried out by means of the Jar-Test equipment followed by direct filtration with downflow using sand filters. Three treatments were performed (A1- Application of 100% Tannin, A2- Application of 100% Ferric Chloride, and A3- Application 50% Tannin + 50% Ferric Chloride). The analyzed parameters were: electrical conductivity; apparent color; turbidity; pH; temperature; total coliforms and Escherichia coli (E. coli). The obtained results for the electrical conductivity did not present significant alteration in any treatment, as well as the pH, which remained within the standards required by Ordinance nº 5 of 2017 Annex XX of the Ministry of Health. The temperature was the only parameter that was no significant difference in the interaction Coagulant * Time. Regarding the removal efficiency, tannin (A1) removed after filtration approximately 98% of apparent color and 97% of turbidity. Treatment A2 showed removal efficiency of approximately 91% for apparent color and 97% for turbidity, while A3 treatment removed 97% and 96%, respectively. In the statistical analysis, the interaction between Coagulant * Time had no significant effect, indicating that the effect of time did not change significantly as a function of coagulants, especially for organic coagulant. The demonstration of similar data between tannin and ferric chloride enables the use of organic coagulant because it is of natural origin, does not cause negative effects to the environment and to humans, becoming a potential alternative for the treatment of water for supply.